Speed of the bacterial flagellar motor near zero load depends on the number of stator units. - Nord, A; Sowa, Y; Steel, B; Lo, C; Berry, R (National Academy of Sciences, 2017)
The bacterial flagellar motor (BFM) rotates hundreds of times per second to propel bacteria driven by an electrochemical ion gradient. The motor consists of a rotor 50 nm in diameter surrounded by up to 11 ion-conducting stator units, which exchange between motors and a membrane-bound pool. Measurements of the torque-speed relationship guide the development of models of the motor mechanism. In contrast to previous reports that speed near zero torque is independent of the number of stator units, we observe multiple speeds that we attribute to different numbers of units near zero torque in both Na+- and H+-driven motors. We measure the full torque-speed relationship of one and two H+ units in Escherichia coli by selecting the number of H+ units and controlling the number of Na+ units in hybrid motors. These experiments confirm that speed near zero torque in H+-driven motors increases with the stator number. We also measured 75 torque-speed curves for Na+-driven chimeric motors at different ion-motive force and stator number. Torque and speed were proportional to ion-motive force and number of stator units at all loads, allowing all 77 measured torque-speed curves to be collapsed onto a single curve by simple rescaling.